2013
DOI: 10.5194/acp-13-4737-2013
|View full text |Cite
|
Sign up to set email alerts
|

How much CO was emitted by the 2010 fires around Moscow?

Abstract: The fires around Moscow in July and August 2010 emitted a large amount of pollutants to the atmosphere. Here we estimate the carbon monoxide (CO) source strength of the Moscow fires in July and August by using the TM5-4DVAR system in combination with CO column observations of the Infrared Atmospheric Sounding Interferometer (IASI). It is shown that the IASI observations provide a strong constraint on the total emissions needed in the model. Irrespective of the prior emissions used, the optimised CO fire… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 29 publications
4
65
1
Order By: Relevance
“…Our results suggest that both GFED4.1s and GFASv1.0 considerably underestimate BB NOx emissions (by 33% and 30%, respectively, relative to our estimate for the VOCbyNOx case) and that the difference between our emission estimate and the respective inventory data cannot be explained by statistical uncertainties in our estimates. This finding is qualitatively consistent with the results of other studies (see, e.g., [19][20][21]36]) where those inventories were found to underestimate emissions of other species (such as CO and aerosol) from wildfires in Russia. It should be kept in mind, however, that the confidence intervals shown in Figure 9 may not fully account for possible biases in our estimates due to several factors mentioned above, including uncertainties in the VOC BB emissions and in background NO2 column amounts, probable negative biases in the satellite NO2 retrievals for the strongly polluted scenes, possible inconsistencies between the NO2 vertical profiles used in the retrieval and predicted by our model, as well as possibly insufficient spatial and temporal representativeness of the observational constraints provided by the available NO2 satellite measurements to BB NOx emissions.…”
Section: Nox Emission Estimatessupporting
confidence: 83%
See 1 more Smart Citation
“…Our results suggest that both GFED4.1s and GFASv1.0 considerably underestimate BB NOx emissions (by 33% and 30%, respectively, relative to our estimate for the VOCbyNOx case) and that the difference between our emission estimate and the respective inventory data cannot be explained by statistical uncertainties in our estimates. This finding is qualitatively consistent with the results of other studies (see, e.g., [19][20][21]36]) where those inventories were found to underestimate emissions of other species (such as CO and aerosol) from wildfires in Russia. It should be kept in mind, however, that the confidence intervals shown in Figure 9 may not fully account for possible biases in our estimates due to several factors mentioned above, including uncertainties in the VOC BB emissions and in background NO2 column amounts, probable negative biases in the satellite NO2 retrievals for the strongly polluted scenes, possible inconsistencies between the NO2 vertical profiles used in the retrieval and predicted by our model, as well as possibly insufficient spatial and temporal representativeness of the observational constraints provided by the available NO2 satellite measurements to BB NOx emissions.…”
Section: Nox Emission Estimatessupporting
confidence: 83%
“…We focused on the disastrous mega-fire event that took place in the European part of Russia in 2010. Emissions of some pollutants (such as CO and aerosol) from the Russian 2010 fires were already investigated using inverse methods (e.g., [19][20][21]), but, to the best of our knowledge, there have yet been no similar studies focusing on NOx emissions from those fires.…”
Section: Introductionmentioning
confidence: 99%
“…In the tropics the CO maximum is mainly associated with fires occurring in the Amazon basin, in central and southern Africa and sometimes over Australia, with maximum in August-November. Major fires occurring in Russia in August 2010 (Yurganov et al, 2011;Krol et al, 2013;R'Honi et al, 2013) and in Siberia in July 2012 (Ponomarev, 2013) are also visible on the zonal mean total column plots. The associated DOFS distributions (right panels of Fig.…”
Section: Global Scale Comparisonmentioning
confidence: 92%
“…The CO total columns have been validated for different locations and atmospheric conditions (e.g., De Wachter et al, 2012;Kerzenmacher et al, 2012), and the comparisons with other data have shown good overall agreement, even if some discrepancies were found within COenriched plumes (reaching 12 % over the Arctic in summer, see Pommier et al, 2010; and reaching 17 % in comparison with other IR sounders, see George et al, 2009). These data were also used previously to study biomass burning plumes (e.g., Turquety et al, 2009;Pommier et al, 2010;Krol et al, 2013;Whitburn et al, 2015).…”
Section: The Co Retrieval Characteristicsmentioning
confidence: 85%